Chemical Strain of Graphite-Based Anode during Lithiation and Delithiation at Various Temperatures - Zeyu Xu; Xiuling Shi; Xiaoqiang Zhuang; Zihan Wang; Sheng Sun; Kaikai Li; Tong-Yi Zhang (Research, 2021)
Electrochemical lithiation/delithiation of electrodes induces chemical strain cycling that causes fatigue and other harmful influences on lithium-ion batteries. In this work, a homemade in situ measurement device was used to characterize simultaneously chemical strain and nominal state of charge, especially residual chemical strain and residual nominal state of charge, in graphite-based electrodes at various temperatures. The measurements indicate that raising the testing temperature from 20°C to 60°C decreases the chemical strain at the same nominal state of charge during cycling, while residual chemical strain and residual nominal state of charge increase with the increase of temperature. Furthermore, a novel electrochemical-mechanical model is developed to evaluate quantitatively the chemical strain caused by a solid electrolyte interface (SEI) and the partial molar volume of Li in the SEI at different temperatures. The present study will definitely stimulate future investigations on the electro-chemo-mechanics coupling behaviors in lithium-ion batteries.